2004
DOI: 10.1002/adsc.200404065
|View full text |Cite
|
Sign up to set email alerts
|

Planar Chiral PHANOLs as Double Hydrogen Bonding Donor Organocatalysts: Synthesis and Catalysis

Abstract: Abstract:4,12-Dihydroxy[2.2]paracyclophanediol (PHANOL; 1), and its para-substituted derivatives 2, 5 and 7, were found to catalyse Diels-Alder cycloadditions of a,b-unsaturated aldehydes or ketones with dienes and/or epoxide ring opening reactions with amines. The mode of catalysis by the PHANOLs is via double hydrogen bonding to the two sp 2 lone pairs of a carbonyl group or the two lone pairs of the epoxide. The order of activity of the PHANOLs for catalysis of the Diels-Alder reaction essentially correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…[7] The activation of substrates by small organic molecules through covalent-or Brønsted acid interactions has been proved as a complementary approach to transition-metal catalysis. [8] Hydrogen-bond catalysis [9] has attracted considerable attention.…”
Section: Introductionmentioning
confidence: 99%
“…[7] The activation of substrates by small organic molecules through covalent-or Brønsted acid interactions has been proved as a complementary approach to transition-metal catalysis. [8] Hydrogen-bond catalysis [9] has attracted considerable attention.…”
Section: Introductionmentioning
confidence: 99%
“…The reactions to form 2 and 3 were elucidated by Cram and Reich . Compounds 70 , 74 , and 76 were elucidated by Braddock and co‐workers . Compound 72 was prepared by Gray and Boekelheide …”
Section: Symmetrically Tetrasubstituted Pcs With Heterosubstituentmentioning
confidence: 99%
“…In their synthesis of a hydrogen‐bonding chiral organocatalyst, Braddock and co‐workers found that the dinitration of 68 proceeds para selectively, as did the chorosulfination of diacetate 75 . The diacylation of diol 73 proceeded in the ortho position regioselectively . Gray and Boekelheide found the chloromethylation of diester 71 to proceed pseudo‐ gem regioselectively, when they elaborated on the synthesis of [2.2.2.2](1,2,4,5)cyclophane …”
Section: Symmetrically Tetrasubstituted Pcs With Heterosubstituentmentioning
confidence: 99%
“…12 A search for additional structural support for the interaction between phenolic diols and carbonyl groups uncovered an X-ray crystal structure reported by Saied, Simard, and Wuest of a diarylacetylenediol bound to a cyclohexanone by dual hydrogen bonds (Figure 1). 13 We recapitulated the essential features of this complex in silico using DFT calculations within Spartan'08 molecular modeling program.…”
Section: Introductionmentioning
confidence: 98%